2021
DOI: 10.56536/ijmres.v11i1.132
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Fluctuations in Public Revenue and Expenditures on Economic Growth in Pakistan: An Impulse Response Approach

Abstract: Allocation of public revenue among productive and non-productive expenditure and its impact on GDP are not extensively studies in Pakistan. In this study, we examine the relationship between government revenue, productive and nonproductive expenditure and economic growth and sustainability over the period of 1978-2018 with the help of Johansen co-integration, error correction test and Impulse Response Function. The result of the study affirms a significant long run and the short run relationship between the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Metallothioneins can be categorized as low molecular weight proteins of highly variable structure, rich in cysteine and with high affinity in forming complexes with PTEs, while they are mainly found in the cytoplasm. Experimental data indicated that metallothionein effectively reduced the toxic symptoms from Cu, Zn, Cd and As by complexing the metals and mediating their transport to the vacuoles [80]. Contrary to the enzyme mediated synthesis of phytochelatin, metallothionein synthesis occurs after translation of the mRNA coding metallothionein structure [55].…”
Section: Metallothioneinmentioning
confidence: 99%
“…Metallothioneins can be categorized as low molecular weight proteins of highly variable structure, rich in cysteine and with high affinity in forming complexes with PTEs, while they are mainly found in the cytoplasm. Experimental data indicated that metallothionein effectively reduced the toxic symptoms from Cu, Zn, Cd and As by complexing the metals and mediating their transport to the vacuoles [80]. Contrary to the enzyme mediated synthesis of phytochelatin, metallothionein synthesis occurs after translation of the mRNA coding metallothionein structure [55].…”
Section: Metallothioneinmentioning
confidence: 99%
“…Type-1 pMTs have 12 Cys residues, type-2 pMTs have 14 Cys residues, type-3 pMTs have 10 Cys residues, and type-4 pMTs have 17 Cys residues. The Cys residues in type-1-3 pMTs are grouped into two domains, whereas the Cys of type-4 pMTs are grouped into three domains [11][12][13]. In addition, some plant MTs have histidine (His, H) residues, which is not a common feature of MTs.…”
Section: Introductionmentioning
confidence: 99%